2009
DOI: 10.1590/s1413-86702009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high risk human papillomavirus cervical infections by the hybrid capture in Asunción, Paraguay

Abstract: Cervical cancer is the most frequent malignant tumour of women in Latin America being human papillomavirus (HPV) the main cause. The aim of this study was to increase the knowledge about the cervical infections with oncogenic HPV types (HR-HPV) in Asuncion, Paraguay. Two hundred and seventy-two cervical samples were analyzed using hybrid capture II assay (HCA II) for HR-HPV. The frequency of HR-HPV in the study group was 44%. HR-HPV was detected in 25% of the women negative for squamous intraepithelial lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Más de 120 genotipos han sido identificados y aproximadamente 40 infectan el tracto anogenital femenino y masculino. Han sido clasificados de acuerdo con el potencial para provocar cambios malignos en el epitelio cervical en VPH de alto riesgo (VPH-AR), como VPH- 16 (2)(3)(4)(5).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Más de 120 genotipos han sido identificados y aproximadamente 40 infectan el tracto anogenital femenino y masculino. Han sido clasificados de acuerdo con el potencial para provocar cambios malignos en el epitelio cervical en VPH de alto riesgo (VPH-AR), como VPH- 16 (2)(3)(4)(5).…”
Section: Introductionunclassified
“…El 25% de las mujeres con citología negativa para lesión intraepitelial escamosa y el 72% de las mujeres con células escamosas atípicas de significado incierto fueron positivas para VPH-AR. Esto demuestra la alta sensibilidad de la prueba para detectar la infección incluso en tejidos de apariencia normal, corroborando que el uso de la citología junto a la HC II podría incrementar la eficiencia de los programas de tamizaje de cáncer de cuello uterino (16).…”
Section: Introductionunclassified
“…The Amazonas state in northern Brazil is an area with a high incidence rate of cervical cancer 14 Using a DNA microarray, in total 22 different HPV types; 14 high-risk HPV (16,18,31,33,35,39,45,51,52,53,56,58,59 and 66) and 8 low-risk HPV (6,42,43,44,54, 61, 72 and 81) were differentiated; 17 types among the Rio Madeira women and 13 types among the Rio Negro women.…”
Section: Discussionmentioning
confidence: 99%
“…According to the estimates for 2016 and 2017 3 the incidence rate of cervical cancer is 37/100,000 women in the state of Amazonas alone, ranking cervical cancer the leading malignancy in women. Furthermore, 16,370 new cases of cervical cancer per year nationwide have been estimated for 2018 and 2019 (15/100,000 women).…”
Section: Introductionmentioning
confidence: 99%
“…However, these countries have argued that there is a need to strengthen secondary prevention strategies for the early detection and timely treatment of women at risk. In turn, a series of studies in the region have concluded the need to carry out cytology-based screening differentially, considering the characteristics of the population groups to be intervened [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%